Minimally invasive versus conventional large-bore percutaneous nephrolithotomy in the treatment of large-sized renal calculi: surgeon’s preference? - Abdelhafez, Mohamed; Wendt-Nordahl, Gunnar (Scandinavian journal of urology, 2016)
Objective: The aim of this study was to compare the efficacy and safety of minimally invasive percutaneous nephrolithotomy (MIP) and conventional percutaneous nephrolithotomy (PCNL) in the treatment of patients with large renal stone burden. MIP has proven its efficacy and safety in the management of small renal calculi. However, conventional PCNL is still considered the standard method for treatment of large renal stones in the upper urinary tract. Materials and methods: A search of two longitudinal databases in two tertiary referral centres for complex stone disease identified 133 consecutive patients who were treated by either MIP or PCNL for renal stones 20 mm or larger between January 2009 and August 2012. Clinical data and outcome measures of the two methods were compared by Student’s t test, chi-squared test or Fisher’s exact test. A p value less than 0.05 was considered statistically significant. Results: Operative time was significantly shorter and hospital stay was significantly longer in conventional PCNL compared to MIP (p = 0.002 and < 0.001, respectively). There were no significant differences in primary stone-free rate or complication rate between the two methods. Only higher graded complications (above Clavien grade II) were significantly more common in conventional PCNL (p = 0.02). Conclusion: MIP is equally effective as conventional PCNL in the treatment of large renal calculi. Both methods have a similar complication rate. The shorter operative time in PCNL may be based on the larger diameter and quicker retrieval of large fragments; the longer mean hospital stay may be caused by the handling of the nephrostomy tube. The current data suggest that the choice of the method mainly depends on the surgeon’s preference.
Gesehen am 09.12.2019